Write it right : English 2 for college students - De Guzman, Christopher Alvin M.; Divino, Divina Gracia C.; Grama, Edesa S.; Sual, Coleen C.; Par, Katrina S. (Mandaluyong City, Philippines : Books Atbp. Publishing, Corp., 2016)
This book is designed to help students present quality papers on topics related to their chosen field of study. It is composed of five chapters. The book includes lessons and activities whose of five chapters.
Unit 1. Writing process -- Unit 2. Writing paragraphs -- Unit 3. Writing paragraphs using rhetorical strategies -- Unit 4. Writing Arguments -- Unit 5. Writing a research paper.
Includes bibliographical references.
Keywords: ENGLISH LANGUAGE -- RHETORICAL